2014
DOI: 10.1016/j.celrep.2013.12.016
|View full text |Cite|
|
Sign up to set email alerts
|

Microcephaly-Associated Protein WDR62 Regulates Neurogenesis through JNK1 in the Developing Neocortex

Abstract: Mutations of WD40-repeat protein 62 (WDR62) have been identified recently to cause human MCPH (autosomal-recessive primary microcephaly), a neurodevelopmental disorder characterized by decreased brain size. However, the underlying mechanism is unclear. Here, we investigate the function of WDR62 in brain development and the pathological role of WDR62 mutations. We find that WDR62 knockdown leads to premature differentiation of neural progenitor cells (NPCs). The defect can be rescued by wild-type human WDR62, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 39 publications
13
102
0
Order By: Relevance
“…[16][17][18] In support of a requirement for WDR62 in mammalian brain development, the depletion of WDR62 decreased mouse brain volume, reduced the proliferation of neural progenitor cells (NPCs) and increased spindle instability. 19,20 Similarly, in utero depletion of WDR62 in embryonic mouse brain also caused premature differentiation of NPCs into immature neurons. 19,21 In characterizing the mitotic functions of WDR62, the ectopic expression of mutant proteins recapitulating MCPH-associated gene changes resulted in perturbed localization to the spindle pole which suggests that the localization of WDR62 and its interacting partners at spindle poles is important for normal mitosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] In support of a requirement for WDR62 in mammalian brain development, the depletion of WDR62 decreased mouse brain volume, reduced the proliferation of neural progenitor cells (NPCs) and increased spindle instability. 19,20 Similarly, in utero depletion of WDR62 in embryonic mouse brain also caused premature differentiation of NPCs into immature neurons. 19,21 In characterizing the mitotic functions of WDR62, the ectopic expression of mutant proteins recapitulating MCPH-associated gene changes resulted in perturbed localization to the spindle pole which suggests that the localization of WDR62 and its interacting partners at spindle poles is important for normal mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Similarly, in utero depletion of WDR62 in embryonic mouse brain also caused premature differentiation of NPCs into immature neurons. 19,21 In characterizing the mitotic functions of WDR62, the ectopic expression of mutant proteins recapitulating MCPH-associated gene changes resulted in perturbed localization to the spindle pole which suggests that the localization of WDR62 and its interacting partners at spindle poles is important for normal mitosis. 16,22 WDR62 was first characterized as an interacting partner of c-Jun N-terminal kinases (JNK) involved in regulating stress signaling.…”
Section: Introductionmentioning
confidence: 99%
“…JNK signaling, together with WDR62, has been shown previously to take part in the control of neurogenesis 5 and JNK-mediated phosphorylation of WDR62 in the C-terminal negatively regulated its microtubule association. 6 The authors showed in this study that JNK-mediated phosphorylation of WDR62 may not be required for the mitotic localization of WDR62.…”
mentioning
confidence: 99%
“…The authors adopted CRISPR technique to generate WDR62 ko AD293 cells and found in them the multipolar spindles, abnormal spindle morphology as reported for WDR62 knockdown and knockout in neuronal progenitors. 4,5 Interestingly, wildtype WDR62, but not those defective in AURKA-dependent phosphorylation can rescue the mitotic defects. In addition, AURKA mainly phosphorylates WDR62 at the N-terminal in M phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation